Analisis Kasus Eksekusi Jaminan Hak Tanggungan Dalam Perkara Kredit Macet Dengan Menimbang Pada Undang-Undang Nomor 4 Tahun 1996 Tentang Hak Tanggungan - Raffi Ikzaaz Abdallah; Kaleb Otniel Aritonang; Abyan Hafizd Naufal; Affan Adyuanas; Dwi Desi Yayi Tarina (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to analyze the application of Law Number 4 of 1996 concerning Mortgage Rights in cases of collateral execution in bad debt cases, with a focus on legal certainty and legal protection for the parties. The research method used is normative analysis with a case study through a normative juridical approach, namely analyzing relevant laws and regulations and relating them to a concrete case in Supreme Court Decision Number 3209 K/Pdt/2012. The results of the study show that although the Security Rights Law has provided a strong legal basis for the execution of security rights, in practice there are still obstacles in enforcing legal certanity, especially regarding execution procedures and the protection of debtor rights. This study emphasizes the importance of legal certainty in the execution of mortgage rights as a guarantee for the stability of the banking system and the protection of the rights of parties involved in credit agreements.